2004
DOI: 10.4049/jimmunol.173.9.5485
|View full text |Cite
|
Sign up to set email alerts
|

Specificity-Based Negative Selection of Autoreactive B Cells during Memory Formation

Abstract: Autoreactive B cells are not completely purged from the primary B cell repertoire, and whether they can be prevented from maturation into memory B cells has been uncertain. We show here that a population of B cells that dominates primary immune responses of BALB/c mice to influenza virus A/PR/8/34 hemagglutinin (HA) are negatively selected in transgenic mice expressing PR8 HA as an abundant membrane-bound Ag (HACII mice). However, a separate population of B cells that contains precursors of memory B cells is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Interestingly, the subsequent fate of these autoreactive HA-specific B cells can differ dramatically in different HA Tg lineages; in HA104 mice (which express HA driven by an SV40 promoter/enhancer), memory responses to secondary virus immunization were comparable to those of BALB/c mice, indicating that PR8 HA-specific B cells could undergo memory formation despite overt autoreactivity (30). By contrast, PR8 HA-specific B cells were subjected to negative selection during memory formation in HACII mice, which express high levels of PR8 HA driven by an MHC class II promoter, including by B cells themselves (19). These studies indicated that specificity for a self-Ag can prevent autoreactive memory B cells that evade negative selection from the primary B cell repertoire from maturing into memory B cells, but that the ability to mediate this form of negative selection can be influenced by the amount and/or cell type in which a self-Ag is expressed.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Interestingly, the subsequent fate of these autoreactive HA-specific B cells can differ dramatically in different HA Tg lineages; in HA104 mice (which express HA driven by an SV40 promoter/enhancer), memory responses to secondary virus immunization were comparable to those of BALB/c mice, indicating that PR8 HA-specific B cells could undergo memory formation despite overt autoreactivity (30). By contrast, PR8 HA-specific B cells were subjected to negative selection during memory formation in HACII mice, which express high levels of PR8 HA driven by an MHC class II promoter, including by B cells themselves (19). These studies indicated that specificity for a self-Ag can prevent autoreactive memory B cells that evade negative selection from the primary B cell repertoire from maturing into memory B cells, but that the ability to mediate this form of negative selection can be influenced by the amount and/or cell type in which a self-Ag is expressed.…”
mentioning
confidence: 97%
“…PevHA, HACII, and TS1 mice have been previously described (19,31,32) and were backcrossed to BALB/c mice (Harlan Sprague Dawley) at least 10 generations before use in these experiments. All mice were maintained under specific pathogen-free conditions using sterile microisolators at The Wistar Institute Animal Facility.…”
Section: Micementioning
confidence: 99%
See 3 more Smart Citations